The price of liquidity: bank characteristics and market conditions - Falko Fecht; Kjell G. Nyborg; Jörg Rocholl (Center for Economic Studies and ifo Institute (CESifo), 2009)
We study differences in the price paid for liquidity across banks using price data at the individual bank level. Unique to this paper, we also have data on individual banks' reserve requirements and actual reserve holdings, thus allowing us to gauge the extent to which a bank is short or long liquidity. We find that the price a bank pays for liquidity depends on the liquidity positions of other banks, as well as its own. There is evidence that liquidity squeezes occasionally occur and short banks pay more the larger is the potential for a squeeze. The price paid for liquidity is decreasing in bank size and small banks are more adversely affected by an increased potential for a squeeze. Contrary to what one might expect, banks in formal liquidity networks do not pay less.
Keywords: G1; G21; E5; D44; 330; Liquidity; banking; squeezes; money markets; repo auctions; Bankenliquidität; Geldmarkt; Pensionsgeschäft; Zins; Bankensystem; Deutschland